A Memory/Immunology-Based Control Approach with Applications to Multiple Spacecraft Formation Flying. (2nd May 2013) - Weng, Liguo; Xia, Min; Hu, Kai; Qiao, Zhuhan
Abstract : This paper addresses the problem of formation control for multiple spacecrafts in Planetary Orbital Environment (POE). Due to the presence of diverse interferences and uncertainties in the outer space, such as the changing spacecraft mass, unavailable space parameters, and varying gravity forces, traditional control methods encounter great difficulties in this area. A new control approach inspired by human memory and immune system is proposed, and this approach is shown to be capable of learning from past control experience and current behavior to improve its performance. It demands much less system dynamic information as compared with traditional controls. Both theoretic analysis and computer simulation verify its effectiveness.